EMPOWERMENT OF EARLY CHILDHOOD EDUCATION TEACHERS THROUGH TRAINING IN THE USE OF CANVA FOR CREATING TEACHING MEDIA - Iffatur Rocmah, Luluk; Rindaningsih, Ida; Ratna Indra Astutik , Ika; Zahrotun Nisa’ , Gitsa (Antis-publisher, 2025)
Objective: To enhance teachers' creativity in creating poster-based learning media by training them to use the Canva application, focusing on the flipped classroom method. Method: The training was conducted at SMA Muhammadiyah 2 Sidoarjo on August 21, 2024, targeting IGABA teachers. Following the training, a mentoring program ran from August 22 to 27, 2024, to assist teachers in designing poster media. Evaluation encompassed three aspects: material usefulness, flipped classroom implementation, and creativity in design. Results: The training significantly improved teachers' understanding and skills in utilizing Canva for learning media. Participants demonstrated enhanced creativity and innovation, contributing to improved learning quality and increased student motivation. Novelty: This initiative integrates Canva application training with the flipped classroom approach to foster creativity among early childhood education teachers, addressing the need for innovative teaching strategies in the digital era.